JPE Turnaround Times, Previous Two Years (Journal of Political Economy, 2021)
Previous articleNext article FreeJPE Turnaround Times, Previous Two YearsPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJPE Turnaround Times, Previous Two Years Outcome of 1st Round DecisionsMean Days to DecisionMedian Days to DecisionDecision Later than Six Months after Submission (as percentage of decisions within decision type)Desk Rejection50%1070%Reject with Reviews42%11710013%Revise8%17515941%Average time from original submission to acceptance (omitting time with author in revision) = 441 days View Table Image Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 2February 2021 Article DOIhttps://doi.org/10.1086/713093 Views: 205 © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.